Shocking Stuff: Technology, Hours, and Factor Substitution. Issue 1 (1st February 2014) - Cantore, Cristiano; León-Ledesma, Miguel; McAdam, Peter; Willman, Alpo
Abstract: The response of hours to technology shocks is a key controversy in macroeconomics. We show that differences between RBC and NK models hinge on highly restrictive views of technology. We introduce CES production technologies and demonstrate that the response of hours depends on the factor-augmenting nature of shocks and the capital–labor substitution elasticity in both models. We develop analytical expressions to establish the thresholds determining its sign. This opens new margins for shock identification combining theory and VAR evidence. We discuss how our models provide new robust restrictions for empirical work, especially using the labor income share.